Biosynthetically Distinct Cytotoxic Polyketides from Setophoma terrestris. Issue 1 (31st October 2014) - El‐Elimat, Tamam; Figueroa, Mario; Raja, Huzefa A.; Graf, Tyler N.; Swanson, Steven M.; Falkinham, Joseph O.; Wani, Mansukh C.; Pearce, Cedric J.; Oberlies, Nicholas H.
Abstract: Sixteen polyketides belonging to diverse structural classes, including monomeric/dimeric tetrahydroxanthones and resorcylic acid lactones, were isolated from an organic extract of a fungal culture Setophoma terrestris (MSX45109) by bioactivity‐directed fractionation as part of a search for anticancer leads from filamentous fungi. Of these, six were new: penicillixanthone B (5 ), blennolide H (6 ), 11‐deoxyblennolide D (7 ), blennolide I (9 ), blennolide J (10 ), and pyrenomycin (16 ). The known compounds were: secalonic acid A (1 ), secalonic acid E (2 ), secalonic acid G (3 ), penicillixanthone A (4 ), paecilin B (8 ), aigialomycin A (11 ), hypothemycin (12 ), dihydrohypothemycin (13 ), pyrenochaetic acid C (14 ), and nidulalin B (15 ). The structures were elucidated by a set of spectroscopic and spectrometric techniques: the absolute configurations of compounds1 –10 were determined by ECD spectroscopy combined with time‐dependent density functional theory (TDDFT) calculations, whereas a modified Mosher's ester method was used for compound16 . The cytotoxic activities of compounds1 –15 against the MDA‐MB‐435 (melanoma) and SW‐620 (colon) cancer cell lines were evaluated. Compounds1, 4, and12 were the most potent, with IC50 values ranging from 0.16 to 2.14 μM . When tested against a panel of bacteria and fungi, compounds3 and5 showed promising activity against the Gram‐positive bacterium Micrococcus luteus, with MIC values of 5 and 15 μg mL –1, respectively. Abstract : Sixteen polyketides, six of them new, were isolated from a fungal culture ( Setophoma terrestris ). Cytotoxicity assays were used to develop structure–activity relationships amongst the series.